A study on decision making conflict in manufacturing industry - Siti Nursyafika, Othman (2014)
Each person often faces a decision making situations. Decision making is part of life and become our importance life factors. It is not an easy matters instead we should consider the cause and effect from some decisions. In the organization, the decision must to confirmation from all parties. This is because the decision taken will ensure the achievement of the organization. During in process to make decision, conflict will occur. The objective of this study are about to focus on the causes of decision making conflict within the organization and to investigate the relationship between causes of conflict with decision making. Some method was used to solve the problem. The result from the analysis has shown to fulfill the objective of the study. Conflict is interaction processes that occur when there is incompatibility between two opinions exist. Making decision can take a long time during the conflict.